Concurrent validity testing of the patient perspective of arrhythmia questionnaire - Kathryn A. Wood; Yutong Jin; Robert T. Krafty; Jameze H. James; Sivaraman K. Iyer; Nitish Badhwar (Health and Quality of Life Outcomes)
Abstract Background Disease-specific patient reported outcome measures (PROMs) are widely used to evaluate not only a patient’s view of their symptoms, functional status, and health related quality of life, but also clinical benefit of treatments. The Patient Perspective of Arrhythmia Questionnaire (PPAQ) was initially developed as a self-administered, disease-specific PROM for patients with supraventricular tachycardia (SVT) assessing the impact of the arrhythmia and symptoms on patients’ daily activities and physical, emotional, and social functioning. Preliminary evidence of content and construct validity has been previously demonstrated, but only in SVT patients in the U.S. and Poland. The aim of this study was to further evaluate the concurrent validity of the PPAQ in patients having a variety of arrhythmias and to explore whether differences in symptoms existed by gender. Methodology In this cross-sectional study, adult cardiac arrhythmia outpatients from a tertiary care, academic medical center completed the 6-item PPAQ, the SF-12, a Fatigue Visual Analog Scale (VAS), the Brief Symptom Inventory (BSI), and the Patient Health Questionnaire (PHQ-9). Included were patients with atrial fibrillation (82.4%), ventricular tachycardia (15.7%), and atrial tachycardia (2%). Descriptive statistics and independent t-tests, pairwise comparisons with Pearson correlations, Goodman Kruskal gamma statistic for ordinal associations, Cronbach’s alpha, and Kuder-Richardson-20 (KR-20) were used to determine concurrent construct validity and internal consistency reliability. Results Participants (n=51) had a mean age of 59.4 years (± 12.6), were majority male (66.7%) and Caucasian (75%). Preliminary evidence of concurrent construct validity was found based on moderate to strong correlations (range from 0.4 to 0.7) between the PPAQ and other validated measures, as well as strong internal reliability (KR-20 of 0.80 and Cronbach’s alpha of 0.91). The most common symptoms reported were fatigue (60.8%) and heart fluttering (52.9%). Blurred vision (p<0.04), dizziness (p<0.01), and fatigue (p<0.04) were seen significantly more frequently in men compared to women. Conclusions Results present additional evidence of the validity and reliability of the PPAQ. The PPAQ comprehensively measures the burden of the disease from cardiac arrhythmia patients’ perspective. Validated, reliable, disease-specific PROMs are needed to direct personalized clinical decision-making.